Non-equilibrium 2, 4-DCP uptake onto pine chips from aqueous solutions - Hossain, S M G (Environmental technology, 2021)
Wide application of 2, 4-dichlorophenol (2, 4-DCP) in industry has resulted in environmental contamination of soils and groundwater. Approaches to cost-effectively remove 2, 4-DCP from water need to be found. 2, 4-DCP uptake onto pine chips from aqueous solution were evaluated in column studies under different particle sizes and flow conditions. The breakthrough curves (BTCs) showed evidence of non-equilibrium with early breakthroughs. The uptake capacity increased from 3.0-6.0 mg g-1 with decreasing flow rate from 10 to 5 mL min-1 but did not show significant differences for particle sizes 1.18 and 4.75 mm at the same flow rate. The BTC for all cases could not be adequately fitted using an equilibrium model with batch derived sorption parameters. They could be better fitted by two site non-equilibrium model using parameters derived from both batch and inverse modelling. At a higher flow rate, the fraction of instantaneous sorption decreased suggesting a higher degree of non-equilibrium. Non-equilibrium processes need to be considered in the design of these types of treatment and operational systems